The 2024 presidential election in the US: Potential impacts on global politics and economics - Pádraig Carmody; Paul S. Ciccantell (EconPol Forum, 2024)
The world is in a period of profound political and economic disruption. The outcome of the US presidential election has the potential to accelerate this or contribute to the construction of a reformed and more legitimate international order. How competition between the US and China is managed will be key to global stability and prosperity. Africa, Europe, and other world regions need to prepare for shocks wrought by a potential Trump victory. The stakes are very high for both the US and the world.
Keywords: 330